Creating flat‐top X‐ray beams by applying surface profiles of alternating curvature to deformable piezo bimorph mirrors. (12th October 2016) - Sutter, John P.; Alcock, Simon G.; Kashyap, Yogesh; Nistea, Ioana; Wang, Hongchang; Sawhney, Kawal
Abstract : A piezo bimorph mirror is deformed into three distinct re‐entrant surface modifications as well as being simply defocused. A re‐entrant modification with seven segments (the maximum possible for this mirror) produces an expanded beam with less striation than a simply defocused beam. Abstract : Beam shaping is becoming increasingly important for synchrotron X‐ray applications. Although routine for visible light lasers, this is challenging for X‐rays due to the limited source coherence and extreme optical tolerances required for the shaping mirrors. In deliberate defocusing, even surface errors <5 nm r.m.s. introduce damagingly large striations into the reflected beam. To counteract such problems, surface modifications with alternating concave and convex curvature on equal segments were polished onto the surface of non‐active mirrors of fixed curvature. Such optics are useful for providing a fixed size of X‐ray beam, but do not provide the adaptability required by many experiments. In contrast, deformable piezo bimorph mirrors permit a continuous range of X‐ray beam sizes and shapes. A new theory is developed for applying non‐periodic modifications of alternating curvature to optical surfaces. The position and length of the segments may be freely chosen. For the first time, surface modifications of alternating curvature are applied to bimorph mirrors to generate non‐Gaussian X‐ray beam profiles of specified width. The new theory's freedom is exploited to choose the segments to match the polishing errors of medium wavelength (>10 mm) and the piezos' influence on the mirror's figure. Five‐ and seven‐segment modifications of alternating curvature are calculated and verified by visible light and X‐ray metrology. The latter yields beam profiles with less striation than those made by defocusing. Remaining beam striations are explained by applying geometrical optics to the deviations from the ideal surface modifications of alternating curvature.